2017
DOI: 10.5146/jcpath.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hpv and p16 expression in the cervical intraepithelial neoplasia

Abstract: Tel: 0 532 302 91 11 (J Curr Pathol. 2017;3:53-9.) ÖZET Amaç: serviks kanseri, önleme programlarına rağmen dünya genelinde kadın ölümlerinin önde gelen nedenlerindendir. bu çalışmanın amacı, servikal intraepitelyal neoplazi ve skuamöz hücreli karsinom olgularında, HPV-HR ve p16 değerlendirilmesi ile sitolojik ve histopatolojik sonuçların karşılaştırılmasıdır. Gereç ve Yöntem:Hastanemiz Patoloji Kliniğinde histopatolojik olarak servikal intraepitelyal neoplazi ve skuamöz hücreli karsinom tanısı almış 51 olgu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…It has been shown that the number of atypical smear diagnoses increase when using TIS ( 5 , 6 ). In studies that compared the TPMM and the TPAM, similar results for ASCUS, LSIL and HSIL diagnoses were noted ( 7–9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the number of atypical smear diagnoses increase when using TIS ( 5 , 6 ). In studies that compared the TPMM and the TPAM, similar results for ASCUS, LSIL and HSIL diagnoses were noted ( 7–9 ).…”
Section: Discussionmentioning
confidence: 99%
“…This technique is more expensive than the classical Pap smear test; however, since it is a more sensitive test, the requirement of longer between-screening intervals balances its higher cost. Liquid-based cytology can decrease the rate of false negative results arising from errors made during screening tests and from interpretation of cytological test results ( 6 ).…”
Section: Introductionmentioning
confidence: 99%